2016
DOI: 10.4103/0019-5413.173521
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of quadruple hamstring graft diameter for anterior cruciate ligament reconstruction by anthropometric measurements

Abstract: Background:The literature is scanty regarding the anthropometric predictors on the diameter of quadruple hamstring graft obtained in anterior cruciate ligament (ACL) reconstruction in Indian population. Minimum diameter of the graft for ACL reconstruction should be >7 mm to preclude failure. The objective of this study was to assess the prediction of the hamstring graft diameter by several anthropometric parameters including age, thigh circumference, weight, height and body mass index (BMI).Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 14 publications
2
25
1
Order By: Relevance
“…A significant correlation between the thigh circumference and the graft diameter of the subjects was observed in the preliminary analysis in our study, but upon further investigation using linear and multiple regressions, only a moderate predictive power for the graft diameter could be ascertained to the measured thigh circumference alone. This is in contrast to the findings of Treme et al and Asif et al, who documented thigh circumference to be a significant predictor of the HT graft diameter [ 17 , 20 ]. Gupta et al also showed a weak correlation between the thigh circumference and the graft diameter [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A significant correlation between the thigh circumference and the graft diameter of the subjects was observed in the preliminary analysis in our study, but upon further investigation using linear and multiple regressions, only a moderate predictive power for the graft diameter could be ascertained to the measured thigh circumference alone. This is in contrast to the findings of Treme et al and Asif et al, who documented thigh circumference to be a significant predictor of the HT graft diameter [ 17 , 20 ]. Gupta et al also showed a weak correlation between the thigh circumference and the graft diameter [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It is interesting to note that, in our study, the patient age was the only independent variable that had a positive correlation with the final graft diameter. The previous studies had demonstrated a negative correlation with age as a predictor of final quadrupled hamstring graft diameter [12,13,23].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with other studies that correlated a relationship between anthropometric data and hamstring autograft size. 1 , 7 , 13 , 17 , 19 , 21 24 In an observational study by Janssen et al 13 of 725 patients, height and weight were most predictive of graft size in men, whereas only height was predictive for women; male sex was also predictive of autograft size. Similarly, Pinheiro et al 19 analyzed 80 patients having ACL reconstruction with hamstring tendons in a quadruple graft and found that graft diameter was related to height, sex, leg and thigh length, weight, and thigh diameter.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, all grafts start with a baseline value of 2 mm, are subtracted by 0.2 mm if female, are increased by 0.5 mm if using a 5-string graft, and require coefficient calculation with the patient’s height and natural logarithm of the BMI. In the Indian Journal of Orthopaedics , Asif et al 1 reported the only other predictive equation based on multiple regression analysis coefficients in a population of 46 patients (44 males, 2 females) and used only height and thigh circumference as parameters. While the coefficients from our regression analysis equation require further prospective comparison and validation, it represents an important first step in preoperatively planning for those with potentially undersized autografts.…”
Section: Discussionmentioning
confidence: 99%